Differential Trends in Hookah Use Among New Jersey Youth - Kulak, Jessica A. (Prev Chronic Dis, 2019)
INTRODUCTION: Use of 2 or more types of tobacco products is common among youth and young adults, highlighting the need for monitoring and intervention activities to encompass products beyond combustible cigarettes. This study documented patterns and trends of ever, current, and frequent hookah use among high school students in New Jersey by other tobacco product use status. METHODS: We analyzed data from the 2008, 2010, 2012, 2014, 2016 waves of the New Jersey Youth Tobacco Survey. Point estimates and 95% confidence intervals described hookah use stratified by use of other tobacco products. Multivariable logistic regression models assessed trends and correlates of hookah use, controlling for the use of other tobacco products and users’ sociodemographic characteristics. Negative binomial regression models examined the association between total number of tobacco products used and hookah use while controlling for sociodemographic variables and survey year. RESULTS: The adjusted odds of current and frequent hookah use among New Jersey high school students were significantly higher in 2014, but not in 2016, compared to 2008. In recent years, hookah use among students who had ever smoked hookah, currently smoked hookah, or frequently smoked hookah was more common among students who had ever or currently smoked cigarettes or e-cigarettes. Hookah users consumed a wider variety of other tobacco products than those who did not use hookah. CONCLUSION: Hookah use remains a public health concern for adolescents; it is more common among users of other tobacco products, especially cigarette and e-cigarette smokers. Questions remain as to whether users of multiple tobacco products are being adequately reached by existing policies and regulations.